Patrick Chamoiseau - Poétiques de la Relation | October 30, 2019 (Conference 2019, 2020)
Patrick Chamoiseau, one of the most important and innovative author of francophone Literature, was invited to present his paper ' Poétiques de la Relation' at the International Conference - “Africa Multiple: Conversations and Building Networks” of University of Bayreuth on October 30, 2019. The conference was designed as a venue to start conversations between representatives from the various institutions that form part of the cluster’s network. The themes selected for the conversations are high on the cluster’s agenda and also at the heart of debates in African Studies today: the premises of knowledge production, African Studies and the question of diasporas, gender and diversity in African Studies, and African Studies in the digital age. - Follow us on Social Media: Facebook - https://www.facebook.com/pg/AfricaMultiple Instagram - https://www.instagram.com/exc2052/ Twitter - https://twitter.com/ClusterAfrica https://www.africamultiple.uni-bayreuth.de/